The differential modulatory effects of Eurotium cristatum on the gut microbiota of obese dogs and mice are associated with improvements in metabolic disturbances. Issue 24 (3rd December 2021) - Lu, Xiaojie; Jing, Yue; Li, Yanyi; Zhang, Naisheng; Zhang, Wenlong; Cao, Yongguo
Abstract : Eurotium cristatum ( E. cristatum ) could reduce obesity in mice and dogs, and the antiobesity effect of E. cristatum can be attributed to gut microbiota. Our study implies that E. cristatum has potential as a probiotic to clinically treat obesity. Abstract : Obesity is a disease in humans and companion animals that can cause many chronic diseases. Eurotium cristatum ( E. cristatum ) is a dominant fungus in Fuzhuan tea. In this study, we aimed to investigate the possibility that E. cristatum may reduce diet-induced obesity by regulating the gut microbiota and measuring the differences in the gut microbiota of obese mice and dogs under E. cristatum supplementation. High-fat diet-fed C57BL/6J mice and beagle dogs were supplemented with live E. cristatum for 8 or 12 weeks. Faecal microbiota transplantation (FMT) and 16S rRNA sequencing were used to evaluate the relationship between the anti-obesity effect of E. cristatum and the gut microbiota. The results suggested that live E. cristatum reduced obesity and metabolic disorders in obese mice and dogs. 16S rRNA sequencing results revealed that E. cristatum decreased the Firmicutes/Bacteroidetes (F/B) ratio and the abundance of members of the Firmicutes phylum, including Lactobacillus gasseri, Lactobacillus reuteri, and Lactobacillus intestinalis, in obese mice, but the opposite was true in obese dogs. Furthermore, to investigate whether the antiobesity effect of E. cristatum can be attributed to gut microbiota, FMT and 16S rRNA sequencing were employed. The FMT trial confirmed that the anti-obesity effect of E. cristatum was mediated by modulating gut dysbiosis. In addition, we isolated live E. cristatum from faeces and found the β-hydroxy acid metabolite of monacolin K (MKA) in E. cristatum culture. Our research implies that E. cristatum has the potential to treat obesity as a novel probiotic.